2009
DOI: 10.1177/008124630903900307
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Processing and Narrative Discourse Production in Children with ADHD

Abstract: Children diagnosed with Attention Deficit Hyperactivity Disorder (ADHD) have cognitive processing difficulties due to their disinhibition and attention deficits, which influence their scholastic performance. Cognitive processing also impacts on the production of oral narratives, an essential skill required for academic success. Therefore the relationship between cognitive processing and oral narratives is investigated. Thirty males, aged 9–11 years, were selected from English medium remedial schools and were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 18 publications
(20 reference statements)
0
15
0
Order By: Relevance
“…For instance, studies focusing on oral evaluations of language may be complicated by non-language-related deficits. Cognitive processing or working memory deficits impact production and comprehension of oral narratives (Moonsamy, Jordaan, & Greenop, 2009; Papaeliou, Maniadaki, & Kakouros, 2012). Thus, investigating language fundamentals, such as receptive or expressive vocabulary, may provide a better picture of actual language skills of children with ADHD that rely more heavily on language than cognitive processing (Wise, Sevcik, Morris, Lovett, & Wolf, 2007).…”
mentioning
confidence: 99%
“…For instance, studies focusing on oral evaluations of language may be complicated by non-language-related deficits. Cognitive processing or working memory deficits impact production and comprehension of oral narratives (Moonsamy, Jordaan, & Greenop, 2009; Papaeliou, Maniadaki, & Kakouros, 2012). Thus, investigating language fundamentals, such as receptive or expressive vocabulary, may provide a better picture of actual language skills of children with ADHD that rely more heavily on language than cognitive processing (Wise, Sevcik, Morris, Lovett, & Wolf, 2007).…”
mentioning
confidence: 99%
“…Children with ADHD tended to have delayed onset of talking in early-childhood [3,4]. In contrast, Barkley, DePaul, and McMurray [5] did not find such differences, while others [6] found that children with ADHD produced good oral narratives skill (in a task requiring the child tell a specific story) regardless of other cognitive processes. They concluded their study about the oral narrative production of ADHD by saying, "Participants in this study produced good oral narratives, implying that their cognitive processing deficits did not appear to affect their narrative production significantly however observations indicated less than adequate planning and attention to the task" (Moonsamy & Jordan,p.…”
Section: Introductionmentioning
confidence: 89%
“…Cognitive processing has also an impact on the production of oral narratives, an essential skill required for academic success. According to Moonsamy et al (2009), narrative measures are useful instruments for oral language evaluation in children with ADHD and the importance of understanding oral narratives within a therapeutic situation is important for both therapist and child.…”
Section: Language and Academic Deficitsmentioning
confidence: 99%